Aplikasi Beberapa Formulasi Bioamelioran terhadap Konsentrasi Hara N, P dan Pertumbuhan Tumpangsari Jagung-Kedelai di Tanah Berpasir Lombok Utara - Astiko, W; Ernawati, NML; Silawibawa, IP (Seminar Nasional Lahan Suboptimal, 2022)
Astiko W, Ernawati NML, Silawibawa IP.  2022. Application of several bioameliorant formulations on nutrient concentrations of N, P and growth of maize-soybean intercropping in sandy soils of North Lombok. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 67-77. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Application of bioameliorants with various formulations can increase nutrient concentration and growth of maize-soybean intercropping. The study was aimed to determine the effect of several bioameliorant formulations on increasing nutrient concentrations and the growth of maize-soybean intercropping. The experimental design used was a randomized block design consisting of five treatments of bioameliorant formulation, namely F0: without bioameliorant, F1: with 10% compost + 10% cattle manure + 10% husk charcoal + 70% mycorrhizal biofertilizer, F2: 15% bioameliorant compost+15% cattle manure+ 15% husk charcoal + 55% mycorrhizal biofertilizer, F3: with bioameliorant 20% compost+20% cattle manure+ 20% husk charcoal + 40% mycorrhizal biofertilizer, F4 : with bioameliorant 25% compost+25% cattle manure + 25% husk charcoal + 25% mycorrhizal biological fertilizer. The variables observed in this study were: (1) soil nutrient concentration variables and plant nutrient uptake (N and P) at 42 days after planting, (2) growth variables included: plant height and number of leaves at 14, 28, 42 and 56 dap, and weight of wet and dry root and shoot at 42 dap, and (3) mycorrhizal population variables included: number of spores and percentage of root infection at 42 dap. The results showed that the application of bioameliorants with a formulation of 25% compost + 25% cattle manure + 25% husk charcoal + 25% mycorrhizal biofertilizer in maize-soybean intercropping gave the best concentrations of N, P and plant growth.